ANALISIS PERKEMBANGAN BISNIS KELUARGA DARI GENERASI MILENIAL KE GENERASI Z DALAM MEWUJUDKAN ADAPTASI TEKNOLOGI, INOVASI, DAN KEBERLANJUTAN BISNIS: STUDI KASUS SHENDA FLORIST - Amanda Citrani Aji; Devinta Nur Arumsari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the development of the family business at Shenda Florist from the Millennial Generation to Generation Z and to explain the role of the successor generation in technology adaptation and business innovation to support business sustainability. This study employed a qualitative approach using a case study method. Data collection techniques were conducted through observation, semi-structured interviews, and documentation involving business owners, successor generation, employees, and customers. Data analysis used the Miles and Huberman model through data reduction, data presentation, conclusion drawing, and data verification. The results showed that business development occurred gradually following the increasing involvement of Generation Z in business management. The changes were reflected through the use of social media, live streaming, websites, and digital recording systems, as well as product and service innovations such as modern bouquets, flower boxes, flower baskets, flower classes, and workshops. In addition, the involvement of Generation Z contributed to increased revenue, market expansion, and stronger business branding. Collaboration between the Millennial Generation and Generation Z created a business management pattern that was more adaptive to technological developments and market needs. This study indicates that Generation Z plays an important role in digital transformation and family business innovation to support business sustainability.